Innovative Electronic Monitoring Device for Termite Activity: Development and Field Evaluation - M.B. Doschanova; S.Y. Babajanova; U.M. Avezova (Zien Journals, 2024)
This paper details the design, development, and evaluation of an electronic monitoring device for detecting termite activity in real time. The device employs a combination of moisture, vibration, and temperature sensors to gather data indicative of termite presence. Field trials conducted in both urban and rural settings demonstrated the device’s accuracy (over 90%) in identifying termite activity. This research underscores the potential of electronic monitoring systems to enhance termite management practices, contributing to more effective and environmentally friendly pest control strategies
Keywords: Termite monitoring; electronic devices; pest management